Promosi Kesehatan dengan Media Leafleat terhadap Perilaku Pencegahan Stunting pada Remaja - Anggarini, Inge Anggi (IKesT Muhammadiyah Palembang, 2025)
Stunting is a public health problem that reflects the condition of failure to thrive in children under five as a result of chronic malnutrition, so that the child's height does not match his age. The movement to improve nutrition for the First 8,000 Days of Life (HPK) is an effort to prevent stunting from pregnancy to adolescence. So it is necessary to know the perceptions of teenagers regarding the problem of stunting so that teenagers can have an important role in giving birth to a stunting-free generation in the future. The community service method is in the form of education or counseling with the title Health Promotion with Leaflet Media on Stunting Prevention Behavior in Adolescents. This activity was held on August 7 2025 at SMA Muhammadiyah III Palembang. During this period, several stages of preparation were carried out and coordinated with related parties and provided education to students at SMA Muhammadiyah III Palembang.